Application of the principal components method for the analysis of heart rate variability - Бабак, В. П.; Чілікин, О. В. (Proceedings of National Aviation University (archive), 2021)
The basic methods used now for the analysis of heart rate variability are considered, the analysis of their lacks is performed. Use of a principal components method for the analysis of heart rate variability is proposed. Its advantages are shown in comparison with existing methods of the analysis.